2011
DOI: 10.1590/s0100-736x2011000300001
|View full text |Cite
|
Sign up to set email alerts
|

Brachiaria spp. poisoning of ruminants in Brazil

Abstract: Brachiaria species are the most important grasses for cattle production in Brazil. However, a limiting factor for the use of Brachiaria spp. is their toxicity. Most outbreaks of hepatogenous photosensitization are caused by B. decumbens; however B. brizantha, B. humidicola and B. ruziziensis can also cause poisoning. The poisoning affects cattle, sheep, goats and buffalo. Sheep are more susceptible than other animal species and the young are more susceptible than adults. There are differences in susceptibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
51
1
31

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(90 citation statements)
references
References 21 publications
(63 reference statements)
5
51
1
31
Order By: Relevance
“…Thus, Riet-Correa et al (7) reported that Brachiaria spp. pastures have varying degrees of toxicity associated with saponin levels, indicating that protodioscin (saponins in Brachiaria decumbens), that when hydrolyzed form sapogenin, diosgenin and yamogenin.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, Riet-Correa et al (7) reported that Brachiaria spp. pastures have varying degrees of toxicity associated with saponin levels, indicating that protodioscin (saponins in Brachiaria decumbens), that when hydrolyzed form sapogenin, diosgenin and yamogenin.…”
Section: Introductionmentioning
confidence: 99%
“…Ha sido reportada en diferentes especies; sin embargo, la mayor presentación de casuística se ha reportado en rumiantes, entre las cuales existen informes de presentación en ovinos (4)(5)(6), caprinos (7), bufalinos (8,9) y bovinos (2,10), de igual forma, se reporta mayor susceptibilidad en ovinos que en bovinos (7), así como la mayor presentación en animales jóvenes que en adultos (11).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…em bovinos, ovinos e, por vezes, em caprinos e búfalos determinam perdas econômicas significativas, especialmente pela queda da produtividade dos animais afetados (Tokarnia et al 2012). Desde 1985, autores têm sugerido que a toxicidade da Brachiaria se deve à presença de saponinas esteroidais litogênicas na gramínea, que são metabólitos glicosilados secundários possivelmente responsáveis por causar lesão hepática e consequente acúmulo de filoeritrina (Opasina 1985, Riet--Correa et al 2011). Entretanto, a formação e o tipo de material armazenado nos macrófagos espumosos presentes no fígado de animais mantidos em pastos de Brachiaria spp.…”
Section: Introductionunclassified
“…Subsequentemente, o número de focos diminuiu, aparentemente devido à morte dos animais susceptíveis ou ao desenvolvimento de resistência à intoxicação. Outra possibilidade seria que a diminuição do núme-ro de surtos fosse resultado da substituição de Brachiaria decumbens que é mais tóxica, por Brachiaria brizantha e Brachiaria humidicola que são menos tóxicas pois contêm níveis menores de saponinas (Riet-Correa et al 2011). As gramíneas do gênero Brachiaria são responsáveis pelo maior percentual de intoxicações em bovino no Mato Grosso do Sul, porém sua importância como planta tóxica é pequena quando se correlaciona o número de surtos com o consumo e área cultivada dessa forrageira (Souza 2015).…”
Section: Introductionunclassified